The Relationship between Knowledge and Medication Adherence in Type 2 Diabetes Mellitus Patients - Aditya, Rico; Putri, Dian Utama Pratiwi; Rahman, Aulia (Global Health Science Group, 2024)
Diabetes Mellitus (DM) is a chronic disease characterized by high blood sugar levels due to the body's inability to produce or use insulin effectively. This disease is one of the top ten causes of death worldwide, and its prevalence continues to rise. Adherence to treatment is crucial for controlling blood sugar levels and preventing serious complications. The aim of this study is to examine the correlation between knowledge and medication adherence in Type 2 Diabetes Mellitus patients at the Sukadana Health Center, East Lampung Regency. This study uses a cross-sectional design with 84 respondents selected through purposive sampling. Data were collected using a questionnaire consisting of two parts: knowledge about diabetes and adherence to treatment. Data were analyzed using the chi-square test and Odds Ratio (OR) calculation. The research results indicate a significant relationship between knowledge about diabetes and medication adherence (p=0.017). Among Type 2 DM patients, 5.5% had high knowledge and high adherence, while 7.4% had low knowledge and low adherence. An Odds Ratio (OR) of 0.010 indicates that respondents with high knowledge were more likely to adhere to treatment compared to those with low knowledge. Therefore, there is a significant relationship between the knowledge of type 2 DM patients and adherence to treatment, with a low level of correlation.